Analysis of Flood-Prone Areas on Bekasi River Watershed - Wijaya, Sri Rasa Nugra Santana; Priyana, Yuli; Priyono, Kuswaji Dwi (International Journal for Disaster and Development Interface, 2023)
Das Kali Bekasi is an area that has physical conditions that support the occurrence of local and natural flood disasters during the rainy season. This research aims to: (1) Determine the distribution of floodprone areas in the Bekasi River Watershed, (2) Find out the most dominant factors of flood vulnerability that occur in the Bekasi River Watershed. The method used in the research is quantitative descriptive analysis. Analyze the data to determine the distribution area prone to flooding by weighting scoring and overlaying rainfall, land use, slope, soil type, and river density. To find out the dominant factors that cause flood vulnerability, a correlation test is used. The results of the research are (1) Flood vulnerability in the Bekasi river basin, based on the results of this research, is divided into 3 classes, namely the not vulnerable class with an area of 82.61 Km² (5.93%), the moderately vulnerable class with an area of 323.85 Km² (23, 26%), very vulnerable class with an area of 985.96 Km² (70.81%). (2) Correlation test to determine the dominant factor causing flooding in the Bekasi River basin and it is known that the dominant factor is the slope parameter, followed by the river density parameter, soil type parameter, land use parameter, and rainfall parameter with the lowest correlation value.